Early Peri-Implant Bone Healing on Laser-Modified Surfaces with and without Hydroxyapatite Coating: An In Vivo Study - Santos, Ana Flávia Piquera [UNESP]; da Silva, Rodrigo Capalbo [UNESP]; Hadad, Henrique [UNESP]; de Jesus, Laís Kawamata [UNESP]; Pereira-Silva, Maísa [UNESP]; Nímia, Heloisa Helena [UNESP]; Oliveira, Sandra Helena Penha [UNESP]; Guastaldi, Antônio Carlos [UNESP]; Queiroz, Thallita Pereira; Poli, Pier Paolo; Barbosa, Debora de Barros [UNESP]; da Silva Fabris, André Luis [UNESP]; et al. (MDPI, 2024)
(1) Objective: The aim of this study was to assess the biological behavior of bone tissue on a machined surface (MS) and modifications made by a laser beam (LS) and by a laser beam incorporated with hydroxyapatite (HA) using a biomimetic method without thermic treatment (LHS). (2) Methods: Scanning electron microscopy coupled with energy-dispersive X-ray spectrometry (SEM/EDX) was performed before and after installation in the rabbit tibiae. A total of 20 Albinus rabbits randomly received 30 implants of 3.75 × 10 mm in the right and left tibias, with two implants on each surface in each tibia. In the animals belonging to the 4-week euthanasia period group, intramuscular application of the fluorochromes calcein and alizarin was performed. In implants placed mesially in the tibiofemoral joint, biomechanical analysis was performed by means of a removal torque (N/cm). The tibias with the implants located distally to the joint were submitted for analysis by confocal laser microscopy (mineral apposition rate) and for histometric analysis by bone contact implant (%BIC) and newly formed bone area (%NBA). (3) Results: The SEM showed differences between the surfaces. The biomechanical analysis revealed significant differences in removal torque values between the MSs and LHSs over a 2-week period. Over a 4-week period, both the LSs and LHSs demonstrated removal torque values statistically higher than the MSs. BIC of the LHS implants were statistically superior to MS at the 2-week period and LHS and LS surfaces were statistically superior to MS at the 4-week period. Statistical analysis of the NBA of the implants showed difference between the LHS and MS in the period of 2 weeks. (4) Conclusions: The modifications of the LSs and LHSs provided important physicochemical modifications that favored the deposition of bone tissue on the surface of the implants.
Keywords: dental etching; dental implants; healing; osseointegration; YAG lasers